Saques e transações presencias em agências bancárias por agricultores familiares e efeito PIX: o caso dos clientes do Agroamigo Crescer - Lima, Lucas de Sousa (2024)
The study examines the way of transacting resources used by family farmers, focusing on the determinants of face-to-face transactions at bank branches, and how these varied after the PIX implementation period. To do this, it uses an information base on the financial movements of farmers in the Agroamigo Crescer Program 60 days after the release of credit from the program in the years 2018 (before) and 2022 (after the PIX). More specifically, this work estimates linear models for the number and percentage of face-to-face transactions at the branch, emphasizing the effects of variables from the post-PIX period and those farmers who reside in municipalities other than their bank branches. The results show a reduction in larger in-person transactions for the latter after the PIX implementation period. Although this has had its share of contribution, it was observed that in-person transactions are still very high and are being replaced for the most part by cash transactions outside the branch (lotteries, for example).